Pancasila and the Existence of a People’s Economy: How Indonesia Facing the Global Capitalism? - Nazila, Elza Ainnun (Indonesian Journal of Pancasila and Global Constitutionalism, 2022)
Globalization is unavoidable for all nations, the existence of globalization triggers the entry of capitalism in the joints of the Indonesian economy. The purpose of this study is to analyze the existence of the implementation of the people's economy as an economic sub-system based on Pancasila to face the onslaught of global capitalism. The method in this paper uses the literature study method, by explaining the theory related to the title, which is obtained from journals, documentation books, and the internet. A people's economy based on Pancasila and the 1945 Constitution and Article 33 is an economic system based on the people's economic strength. Where the manifestation of the people's economy itself is in the form of cooperatives and various economic activities or businesses carried out by the people in practice are in the form of MSMEs. The existence of a populist economy can be realized by prioritizing the principles of kinship and justice based on Pancasila and the role of economic actors as partners, to counteract the currents of global capitalism.